Depth and intensity of the sulfate-methane transition zone control sedimentary molybdenum and uranium sequestration in a eutrophic low-salinity setting - Jokinen Sami A.; Koho Karoliina; Virtasalo Joonas J.; Jilbert Tom (Elsevier Ltd, 2022)
Molybdenum (Mo) and uranium (U) contents in sedimentary archives are often used to reconstruct past changes in seafloor oxygenation. However, their sequestration processes are as yet poorly constrained in low-salinity coastal waters, which often suffer from anthropogenic eutrophication but only mild oxygen depletion. Due to the consequent lack of robust long-term paleo-redox reconstructions in such settings often characterized by a shallow front of dissolved sulfide accumulation within the sediment pore waters, inadequate understanding of the long-term drivers behind oxygen loss impedes cost-effective mitigation of this environmental problem. Here, we investigate the mechanisms of Mo and U sequestration in an oxic, low-salinity coastal setting in the northern Baltic Sea where anthropogenic eutrophication over the 20th century has resulted in formation of a shallow sulfate-methane transition zone (SMTZ) in the sediment column of this brackish-water basin. Our results demonstrate remarkably similar patterns for authigenic Mo and U sequestration, whereby the depth and intensity of the SMTZ exerts a first-order control on their solid-phase uptake. Sequential extraction analysis suggests that a large part of the authigenic Mo pool is hosted by refractory Fe–S phases such as pyrite and nanoscale FeMoS4, implying that the Fe-sulfide pathway is the dominating process of authigenic Mo scavenging. However, we also observe a pool of extremely labile Mo deep within the SMTZ, which might record an intermediate phase in authigenic Mo sequestration and/or partial switch to the organic matter (OM) pathway at low dissolved Fe levels. Authigenic U resides in acid-extractable and refractory phases, likely reflecting uptake into poorly crystalline monomeric U(IV) and crystalline uraninite, respectively. Similarly to Mo, authigenic U uptake is active at two fronts within the SMTZ, paralleled by increases in dissolved sulfide levels, suggesting coupling between sulfide production and U reduction. Our results imply that both Mo and U could provide viable proxies for mild bottom water deoxygenation in these settings, through the indirect link between seafloor oxygen conditions and the depth of SMTZ. Of these, Mo appears to more robustly capture variations in seafloor oxygen levels due to the significantly higher share of the authigenic pool. However, temporal resolution of these proxies is limited by the vertical offset between seafloor and the zone of authigenic uptake, and the superimposed character of the signal at a given depth due to vertical migrations of the SMTZ. These results have important implications for the use of Mo and U as paleo-redox proxies in other low-salinity coastal settings exposed to eutrophication.